PENGARUH MOTIVASI BERKUNJUNG, DAYA TARIK WISATA DAN PROMOSI TERHADAP KEPUTUSAN BERKUNJUNG KE TAMAN MINI INDONESIA INDAH - Laras Nurandriani; Sinthon Siahaan (Panorama Nusantara, 2022)
This study aims to determine the effect of motivation to visit, tourist attraction and promotion on the decision to visit Taman Mini Indonesia Indah partially and f simultaneously. This research was conducted at Taman Mini Indonesia Indah. The data collection technique used was non-probability sampling. The samples taken were 100 respondents with the Accidental Sampling method. The analysis technique used is multiple linear regression using SPSS 20 software. The results of this study indicate that the motivation to visit does not have a positive effect on the decision to visit, tourist attraction has a positive effect on the decision to visit and promotion has a positive effect on the decision to visit, and there is a simultaneous influence on the motivation to visit, tourist attraction and promotion on decisions to visit.